An Evaluation of the Technical, Pure Technical and Scale Efficiencies in the Indian Banking Industry using Data Envelope Analysis. (September 2014) - Tandon, Deepak; Tandon, Kamini; Malhotra, Nidhi
A well-developed and efficient banking sector is the fundamental requirement for smooth functioning of any economy. The present study is an attempt to examine the technical, pure technical and scale efficiencies of the Indian banks across different ownership categories for the period 2009–2012. About 7 out of the 44 banks selected lie on the efficiency frontier and form the reference set for their peers. Further, it is observed that efficiency scores do not vary much across the public sector, private sector and foreign banks. Performance of the public sector and private sector banks is almost at par with respect to technical efficiency whereas in the case of foreign banks, there lays scope for improving scale efficiency. A second stage regression analysis is carried out using Tobit regression to examine the determinants of efficiency. Non-interest income emerges the most important determinant of efficiency of banks in India.